Arthropods discovered in lower and upper pitchers of Nepenthes at Rampa-Sitahuis Hill, North Sumatra, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Tarigan MRM, Corebima AD, Zubaidah S, Rohman F. 2021. Arthropods discovered in lower and upper pitchers of Nepenthes at Rampa-Sitahuis Hill, North Sumatra, Indonesia. Biodiversitas 22: 5358-5366. This research aimed to identify the families of arthropods trapped in the upper and lower pitchers of Nepenthes in Rampa Sitahuis Hill Area, North Sumatra, Indonesia. This descriptive qualitative research used an experimental method of data analysis. The arthropods were obtained from the upper and lower pitchers of N. rafflesiana, N. gracilis, N. eustachya, N. ampullaria, and N. sumatrana. Consequently, ten families of arthropods, namely Culicidae, Formicidae, Araneidae, Calliphoridae, Rhyparochromidae, Salticidae, Curculionidae, Blattellidae, Coccinellidae, and Tridactylidae were identified. Culicidae and Formicidae were the most abundant arthropods trapped in Nepenthes’ lower and upper pitchers because Nepenthes functioned as a microhabitat and breeding ground for Culicidae (adult mosquitoes) and Formicidae (ant larvae). Thus, these species established a mutualistic symbiosis in which ants used the tendrils of Nepenthes to lay their eggs and collected nectar generated by the honey glands, while the egg-laying process aids in the pitcher’s breakdown process.
Keywords: Families; mutualism; predation; specimen identification